2005
DOI: 10.1103/physrevlett.95.203003
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Attosecond Double Ionization Dynamics via Molecular Alignment

Abstract: Access and use of this website and the material on it are subject to the Terms and Conditions set forth at NRC Publications Record / Notice d'Archives des publications de CNRC:http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?action=rtdoc&an=21276198&lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?action=rtdoc&an=21276198&lang=fr READ THESE TERMS AND CONDITIONS CAREFULLY BEFORE USING THIS WEBSITE.http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en Vous avez des questions? Nous pouv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
96
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(106 citation statements)
references
References 29 publications
9
96
1
Order By: Relevance
“…This implies that the second and the fourth quadrant of the p 1 p 2 plane are expected to be populated [16]. A population in such regions of the parallel momentum plane has also been observed for NSDI of diatomic molecules, especially if the molecules in question are aligned perpendicular to the laser-field polarization [19][20][21][22]. Furthermore, it has been recently shown that electron-impact ionization, alone, would not be very useful for retrieving the molecular structure in the experimentally relevant intensity range [23].…”
Section: Introductionmentioning
confidence: 99%
“…This implies that the second and the fourth quadrant of the p 1 p 2 plane are expected to be populated [16]. A population in such regions of the parallel momentum plane has also been observed for NSDI of diatomic molecules, especially if the molecules in question are aligned perpendicular to the laser-field polarization [19][20][21][22]. Furthermore, it has been recently shown that electron-impact ionization, alone, would not be very useful for retrieving the molecular structure in the experimentally relevant intensity range [23].…”
Section: Introductionmentioning
confidence: 99%
“…N 2 represents one of the simplest few-electron diatomic systems, and its interaction with light has been extensively studied experimentally as well as theoretically. A wealth of results has been reported for single-photon interactions (see, e.g., [86,[112][113][114][115][116][117][118][119], fragmentation by intense laser fields [83,84], two-colour time-resolved studies [73], and highresolution electron impact coincidence measurements [120]. Recently, several experiments on multiple ionization of N 2 by few EUV photons have been performed at FLASH and SCSS.…”
Section: Multiple Fragmentation Of N 2 Moleculementioning
confidence: 99%
“…So far most experimental studies of ionization of molecules by ultrashort pulses have made use of the Ti:sapphire laser at ∼800 nm central wavelength [83][84][85][86][87][88][89][90][91][92]. For this wavelength, ionization requires the absorption of many photons, which makes the process highly non perturbative even at relatively low intensities (e.g., 10 12 W/cm 2 ).…”
Section: Ionization Of H 2 By Ultrashort Vuv Laser Pulsesmentioning
confidence: 99%